Three-dimensional IMRT QA of Monte Carlo and full scatter convolution algorithms based on 3D film dosimetry. (September 2021) - Molazadeh, Mikaeil; Robatjazi, Mostafa; Geraily, Ghazale; Rezaeejam, Hamed; Zeinali, Ahad; Shirazi, Alireza
Abstract: This study aimed to evaluate the dose distribution of the Monte Carlo (MC) code and TiGRT treatment planning system (TPS) compared to experimental measurements. A thirteen-field Intensity-Modulated Radiation Therapy (IMRT) plan was created according to the RTOG H-0022 protocol. A film stack at distances of 3 mm and 1 mm was inserted into the phantom and irradiated. The dose distribution by this IMRT plan was also simulated using EGSnrc. The 3D dose distributions obtained from the TPS and MC calculations were compared against the film measurements (gold standard) using gamma index with conventional (3%-3 mm) and strict (2%-2 mm) criteria. The local gamma passing rate (GPR) for TiGRT-film and MC-film with the conventional criteria at the resolution of 3 mm was 89.36% and 97.94% respectively, and with a resolution of 1 mm, the agreement rate increased to 91.83% and 99.23%, respectively. With the strict criteria at the resolution of 1 mm, the percentage of agreements for TiGRT and MC was about 72.55% and 95.27%, respectively. From the research point of view, the 3D film dosimetry can be used as a valuable dosimetry tool for evaluating the 3D dose distribution in dose computing systems. Highlights: 3D film dosimetry procedure in the anthropomorphic head phantom was studied. Dose distribution of FSC algorithm and MC simulation were evaluated using 3D gamma index. Gamma test showed that the result of MC is better than the results of TiGRT TPS. This work demonstrated that 3D film dosimetry could play a key role in IMRT QA.